Nel profondo degli anni Settanta: I diecimila cavalli - Raffaeli, Massimo (L’ospite ingrato, 2024)
This essay reviews the main elements of Roberto Roversi’s novel, I diecimila cavalli (1976). It highlights its peculiar expressive force, its somewhat epic scope and its explosive critical charge, without neglecting the “political” implications of the author’s courageous editorial choices. Roversi’s book is therefore analytically historicized, or inserted into the complex ideological and literary context of the Seventies, with particular reference to the political and cultural movements that manifested themselves vehemently in the city of Bologna and to the intersections of ideas that took place there.